The Evaluation of information system performance in higher education case study with EUCS model at bandar lampung university - Reni Nursyanti; Erlangga ERLANGGA (International Conference on Engineering and Technology Development (ICETD), 2013)
Simperti has been used for about more than 10 years at the bandar lampung university, but the system has’nt been done with the developing which it must be followed the bussiness need in UBL. Sometimes it arises the problem that give obstacles which will give impact to UBL’s academy performance, the management has not been taking any actions to improve the simperti’s performance, especially in terms of user satisfaction that indicate which parts need to be improved to meet the needs of the user, because it has not been done an analysis of the feasibility of the system in terms of the end user.Several models have been built to analyze and understand the factors that influence the acceptance of the use of computer technology, one of them is model developed by doll and torkzadeh(1998), the purpose of this research is to apply the model of end user computing satisfaction in evaluating the higher education information system (SIMPERTI) bandar lampung university. So that evaluation results obtained by simperti based on EUCS dimension, content, accuracy, format, ease of user, topical, system speed, reliability.